Insights into high-efficient removal of tetracycline by a codoped mesoporous carbon adsorbent - Chen, Xinyu; Shi, Shuo; Han, Ximei; Li, Min; Nian, Ying; Sun, Jing; Zhang, Wentao; Yue, Tianli; Wang, Jianlong (Chinese journal of chemical engineering, 2022)
[Display omitted] Adsorbents with simple preparation and high surface area have become increasingly prevalent for the removal of organic contaminants. Herein, a carbon nanoplate codoped by Co and N elements with abundant ordered mesoporous (Co/N-MCs) was applied as an adsorbent for tetracycline removal. Taking integrated advantages of ordered mesopores on carbon-based structures and N-doping inducing the strengthened π–π dispersion and generation of pyridinic N, as well as cobaltic nanoparticles embedded in carbon nanoplates, the Co/N-MCs was tailored for high efficiently absorbing tetracycline via π-π interaction, Lewis acid-base interaction, metal complexation and electrostatic attraction. The Co/N-MCs had the advantages of high surface area, porous structure, plenty adsorption sites, and easy separation. As such, the as-prepared Co/N-MCs adsorbents significantly enhanced tetracycline removal performance with a maximum adsorption capacity of 344.83 mg·g−1 at pH 6 and good reusability, which was finally applied to removal tetracycline from tap water sample. Furthermore, the adsorption process towards tetracycline hydrochloride could be well attributed to the pseudo-second-order kinetic and Langmuir isotherm models. Compared with traditional carbon-based adsorbents, it owns a simpler synthesis method and a higher adsorption capacity, as well as it is a promising candidate for water purification.